Establishment of Optimum Ecological System for Monitoring Boiler Units - V. I. Nazarov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A mathematical model has been proposed for ecological monitoring of a boiler unit. This model makes it possible to obtain maximum decrease in effluents at minimum reduction in economical operational efficiency of the boiler unit.